The Management of Irrigation and Potassium Fertilization to Mitigate the Effect of Light Frosts on the Phenolic and Volatile Compounds in Virgin Olive Oils - Suony Antonelli; Sebastián Pozas; Jorge Saavedra-Torrico; Mauricio Donders; Chris Bustamante; Betsabet Sepúlveda; Francisco Tapia; Diego L. García-González; Nalda Romero (MDPI AG, 2024)
The frequency of early frosts has increased in recent years, which are injurious to olive growing, causing losses in the yield and quality of virgin olive oil. In this research, it was studied how the management of agronomic factors mitigates frost damage in Arbequina olives, minimizing the loss of phenols and volatiles in virgin olive oil, at different fruit ripening stages. A Box-Behnken design and multivariate analysis were performed, with three levels of irrigation, potassium fertilization, and foliar copper application (15 treatments). Virgin olive oil was extracted from fresh and frozen olives. Light frost caused a significant decrease in the total phenols and secoiridoid compounds in and the antioxidant capacity of the frost-affected oils, which were perceived as more pungent and had the slight defect of "frostbitten olives". According to the Box-Behnken design, an 86% reference evapotranspiration (ET0) or higher with 100 potassium oxide units (UK2O) and a 100% ET0 or higher with 250 UK2O would be required to minimize the effect of light frost on phenols and volatiles. Partial Least Squares Regression-Discriminant Analysis (PLS-DA) differentiated the virgin olive oils according to their ripening stage and fresh and frost conditions. Moreover, PLS-DA positively correlated a 75-100% ET0 and 0 Uk2O with the dialdehydic form of the decarboxymethyl ligstroside aglycone (p-HPEA-EDA), the dialdehydic form of the decarboxymethyl oleuropein aglycone (3,4-DHPEA-EDA), the dialdehydic form of the ligstroside aglycone (p-HPEA-EDA-DLA), and with fruity, pungent, and bitter attributes. Precision agronomic management based on the needs of the crop itself would avoid unnecessary stress on olive trees and oil damage.